Quantitative Limbic System Mapping of Main Cognitive Domains in Multiple Sclerosis - Keser, Zafer; Hasan, Khader M.; Mwangi, Benson; Younes, Kyan; Khayat-Khoei, Mahsa; Kamali, Arash; Lincoln, John A.; Nelson, Flavia M. (Frontiers in Neurology, 2018)
Background and Objective: Cognitive impairment (CI) is common in multiple sclerosis (MS) but underlying mechanisms and their imaging correlates are not completely understood. The gray and white matter structures of the limbic system (LS) play crucial roles in different aspects of cognition. To investigate their role in MS related CI, and since a detailed evaluations are lacking in the literature, we used a comprehensive neuroimaging approach to evaluate CI’s correlations with the main components of the LS. Methods: Ten non-cognitively impaired MS patients and 30 MS patients with diagnosed CI, who underwent a comprehensive neuropsychological evaluation were included in the analysis. Microstructural integrity, volumetry of main limbic gray and white matter structures and cortical thickness were assessed for associations with CI. Results: Fornix and cingulum/cingulate cortices were found to be the strongest correlates of CI in MS. As expected LS’gray and white matter structures were involved in various cognitive functions. Uncinate fasciculi showed significant correlation with verbal and visuospatial learning and memory, phonemic and semantic fluency; hippocampi with visuospatial skills, phonemic and semantic fluency, executive functions and processing speed; thalami with verbal learning, visuospatial skills, semantic fluency; and amygdalae with verbal recognition discrimination. Conclusion: This comprehensive neuroimaging approach elucidated the role of the main limbic structures in cognitive functions associated with MS related CI.